Analysis of Slang Words in the Lyrics of "Saint Pablo" by Kanye West: Analisis Kata Bahasa Gaul dalam Lirik "Saint Pablo" Karya Kanye West - Angela, Yola (Jurnal Intelek Insan Cendikia, 2024)
Along with  the  changing  times,  language  also  develops  and  adapts  to  the  current  era.  The development of the language can be in the addition of vocabulary, functions and goals of the language itself.Today, people also use songs as a medium of communication.this triggers your interest in conducting research on the message conveyed in the slang of the song.This research focuses on two types of intervals used by Kanye West in his song Saint Pablo.The analysis is based on 2 types of slang in Chapman theory.Researchers used qualitative methods to collect data by searching the lyrics of Saint Pablo's songs and looking for words that contain slang. The  data in this study were taken from the lyrics of the song Saint Pablo by Kanye West which contains these two types of slang. Then, the researcher classifies them based on the type of figurative language found in the lyrics of the song and then finds the dominant type.In this research, the writer collects 35 data from Kanye West's songs, then classifies them and analyzes them  contextually  and based  on theory.After  conducting research, the researcher  found that Slang words are important to learn and understand the meaning of Slang. Then, of the many words found in Kanye West's song lyrics, the researcher found that the most dominant type of slang was Primary slang.